COVID-19 pandemic and preparedness of anesthesia team in a stand-alone cancer centre in Eastern India - Jyotsna Goswami; Anshuman Sarkar; Sudipta Mukherjee; Pralay S Ghosh; Angshuman R Pal; Suparna M Barman; Sumantra S Banerjee; Rudranil Nandi; Sanjay Bhattacharyya (Wolters Kluwer Medknow Publications, 2021)
India came under the grip of the coronavirus disease-2019 (COVID-19) pandemic and is now seeing rising graph. Cancer patients are specially in the high-risk group because of their immunocompromised status on one hand and progressive disease on the other hand. Hence, cancer care facility needs to prepare a clear strategy to manage their space, staff and supplies so that optimum patient care can be continued in the face of COVID-19 pandemic. In addition, infection prevention measures need to be robust to reduce in-hospital transmission. The working area of anesthesia and Critical Care is spread over the whole hospital such as operating room, ICU, isolation area, out-patient dept (OPD) area, various diagnostic areas and in-patient dept (IPD) to attend code blue calls. In this article, we describe the preparedness and initial response measures of the anesthesia and Critical Care department of a stand-alone tertiary level cancer care centre in eastern part of India. These include engineering controls such as identification and preparation of an isolation operating room, administrative measures such as modification of workflow, introduction and adequate supply of personal protective equipment for staff and formulation of clinical guidelines for anesthetic management. These containment measures are necessary to continue care of cancer patients, optimize the quality of care provided to COVID-19 positive cancer patients and to reduce the risk of viral transmission to other patients or healthcare providers.